Vulnerable Women's Self-Care Needs in Knowledge, Attitude and Practice Concerning Sexually Transmitted Diseases - Nasrollah Alimohammadi; Zahra Baghersad; Zahra Boroumandfar (Shiraz University of Medical Sciences, 2016)
Background: Vulnerable women are prone to sexually transmitted diseases (STD) due to their special conditions and poor knowledge about these diseases in the society. Therefore, the present study aimed to determine the vulnerable women's self-care needs in knowledge, attitude and practice concerning STD. Methods: This is a cross-sectional-descriptive study conducted in 2014. The data collection was carried out using a self-administered structured questionnaire. 120 vulnerable women referring to centers affiliated to health and well-being center in Isfahan participated in this study. They were selected through proportional rationing sampling and filled out a researcher developed questionnaire containing information on personal characteristics, self-care knowledge, attitude, and practice needs toward the STD. The data were analyzed using statistical methods including Spearman & Pearson correlation co-efficient, independent t-test and ANOVA. All analyses were carried out using SPSS, 20. Results: Based on the results, most of the subjects mentioned that their priorities of self-care needs in domains of knowledge, attitude and practice were "familiarization with the types and contamination ways of sexually transmitted diseases" (57.9%); "diagnosis of STD only makes us anxious" (24.8), and "the method of washing the genital area before and after intercourse" 41.3%), respectively. There was a significant association among marital status, education, history of addiction, and self-care needs in domains of knowledge, attitude and practice (P<0.05). Conclusion: Results showed that vulnerable women not only knew their need about STD, but also paid attention to their attitude and practice needs toward STD. Therefore, educational programs should be designed and administrated by the experts, based on vulnerable women's self-care needs concerning their knowledge, attitude and practice to prevent and control STD in vulnerable individuals.